“Is it Safe?” Risk Perception and Drinking Water in a Vulnerable Population - Spence, Nicholas; Walters, Dan (International Indigenous Policy Journal, 2012)
Access to safe drinking water is a pressing social policy issue globally. Despite the milestones reached in this area of Canadian public health, marginalized and vulnerable populations, including those founded on racialized identity, such as First Nations, continue to be plagued by accessibility issues. This work sheds new perspective on the issue, arguing for a research and policy focus that is inclusive of risk perception. A model of risk perception of drinking water is developed and tested for First Nations on reserve in Canada using the 2001 Aboriginal Peoples Survey. It is shown that the analytical use of racialized identity advances understanding of risk perception and the environment (water). Moreover, a large degree of heterogeneity within the First Nation population across a number of social determinants of risk perception illustrates the shortcomings of framing the issue in a simplistic manner (First Nation population versus general population). Implications for risk research, including risk communication & management, and policy are provided.